2006
DOI: 10.2522/ptj.20050266
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Costs and Muscle Activity Patterns During Robotic- and Therapist-Assisted Treadmill Walking in Individuals With Incomplete Spinal Cord Injury

Abstract: Differences in metabolic costs and muscle activity patterns between therapist- and robotic-assisted standing and stepping illustrate the importance of minimizing passive guidance and stabilization provided during step training protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(222 citation statements)
references
References 50 publications
10
197
3
2
Order By: Relevance
“…The results from Israel et al's study indicate that similar muscle activation patterns and metabolic responses can be achieved in the Lokomat when compared with therapist-assisted training [35]. However, this finding only applies when the appropriate instructions or training conditions are given to the subject.…”
Section: Metabolic and Cardiac Responses During Robotic Gait Trainingmentioning
confidence: 69%
See 1 more Smart Citation
“…The results from Israel et al's study indicate that similar muscle activation patterns and metabolic responses can be achieved in the Lokomat when compared with therapist-assisted training [35]. However, this finding only applies when the appropriate instructions or training conditions are given to the subject.…”
Section: Metabolic and Cardiac Responses During Robotic Gait Trainingmentioning
confidence: 69%
“…Israel et al published a recent study that compared muscle activation patterns and metabolic responses in individuals with incomplete SCI who walked on a treadmill with either therapist assistance or Lokomat assistance [35]. Twelve individuals classified as C or D on the American Spinal Injury Association (ASIA) Impairment Scale [ASIA, 2004] were tested on two separate sessions.…”
Section: Metabolic and Cardiac Responses During Robotic Gait Trainingmentioning
confidence: 99%
“…All eight DOFs not only allow the exoskeleton to make a forward stepping motion (as provided by the Lokomat and the AutoAmbulator), but also maintain the fundamental instability of a standing or walking human. As such, balance control still has to be achieved when walking in the device, either by the human or (when necessary) by the robot, and is widely recognized as an important aspect of gait training [8], [20]. Table I describes which DOFs are possible for a human being, which of these are actuated in the robot, which are left free, and which are blocked.…”
Section: A Impedance Controlled Exoskeletonmentioning
confidence: 99%
“…Similarly, Hornby et al [12] found that Lokomat robot-assisted therapy in 62 patients with chronic stroke was not superior to the conventional gait training. Such inconsistent results in the Lokomat robot-assisted studies may result from different experimental design and testing methods utilized [10], lack of volitional neuromuscular control [14], restricted pelvic and trunk movement control [15,16], arm swing, as well as altered acceleration and deceleration from pre-swing to initial contact [17]. …”
Section: End-effector Type Of Robot-assisted Gait Trainingmentioning
confidence: 99%